2008
DOI: 10.2478/s11687-008-0014-3
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of selected heavy metals in Ligula intestinalis L., 1758 plerocercoids (Cestoda) compared to it host’s (Tinca tinca L., 1758) organs from Beyşehir Lake (Turkey)

Abstract: 76 SummaryThe accumulation of heavy metals (Cu, Fe, Zn and Mn) was measured by atomic absorption spectrophotometry in some organs of tench (Tinca tinca L., 1758) and tissues of its parasite collected from Beyşehir Lake, and compared with the data from sediments and water. The Cu levels in L. intestinalis L., 1758 plerocercoids were 1.69 times, respectively, higher than those in fish gill. Zn level in L. intestinalis plerocercoids was 2.13 times higher than those in fish liver, was 5.53 times higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…2008). The bioaccumulation ability of L. intestinalis is higher in R. argentea , however, compared with tench ( Tinca tinca ) from Lakes Kovada (Tekin‐Özan & Kir 2005) and Beysher (Tekin‐Özan & Barlas 2008), both in Turkey. The bioaccumulation of Cd by L. intestinalis in R. argentea is lower than for another cestode ( Monobothrium wageneri ) and Bothriocephalus scorpii in Tinca tinca (Sures et al.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…2008). The bioaccumulation ability of L. intestinalis is higher in R. argentea , however, compared with tench ( Tinca tinca ) from Lakes Kovada (Tekin‐Özan & Kir 2005) and Beysher (Tekin‐Özan & Barlas 2008), both in Turkey. The bioaccumulation of Cd by L. intestinalis in R. argentea is lower than for another cestode ( Monobothrium wageneri ) and Bothriocephalus scorpii in Tinca tinca (Sures et al.…”
Section: Discussionmentioning
confidence: 94%
“…2003; Thielen et al. 2004; Sánchez‐Chardi & Nadal 2007; Tekin‐Özan & Barlas 2008; Eira et al. 2009).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…They hypothesised that this indicated that accumulation of heavy metals in the parasite was a gradual and long-term process which probably occurred during the growing phase of the parasite in the fish host. More recent studies by Tekin-Ozan and co-workers (Tekin-Ozan and Kir, , 2008Tekin-Ozan and Barlas, 2008), utilising Ligula and tench (Tinca tinca), have extended the greater bio-accummulation by the plerocercoid to a more extensive range of heavy metals and speculate that if the parasite reflects the amount of heavy metal contaminants in the water and sediments, it may provide reliable data about pollution in water bodies. Whilst this is perhaps debatable, the value of the association of the plerocercoid with heavy metals probably lies in the size of the parasite which may assist in the elucidation of how parasites can bioaccumulate pollutants with no apparent ill-effects on their biology.…”
Section: T H E P a R A S I T Ementioning
confidence: 99%